Respuestas

  • Usuario de Brainly
2014-01-17T21:20:28+01:00
Solución:

=> -6 + 5 *(-4-12) / (3*(-2)) + 7*3 = -6 + 5* (-16) / (-6) + 21
................................................= - 6 - 80 / -6 + 21
................................................= -6 + 40/3 + 21
................................................= (-18 + 40 + 63) / 3
................................................= 85 / 3 .......Respuesta.

Suerte. Anitagonzalez
2014-01-17T21:24:10+01:00
Sería -6+5-4-12 / 3-2+21 y esto queda en -17/22